2017
DOI: 10.20319/lijhls.2017.31.1834
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antimicrobial Activity of Neocaryamacrophylla Leaves Extract

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The frequency of lifethreatening infections caused by pathogenic microorganisms has increased worldwide and is becoming an important cause of morbidity and mortality especially in developing countries with lower health status indices. Also, the high prevalence of multi-drug resistant strains of bacteria has elevated the threat of untreatable bacterial infections and adds urgency to the hunt for new healing strategies (Isaka et al, 2017). In addition to this problem, antibiotics are sometimes associated with adverse effects on the host, which include hypersensitivity, depletion of beneficial gut and mucosal microorganism, immune suppression and allergic reactions (Namita & Mukesh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of lifethreatening infections caused by pathogenic microorganisms has increased worldwide and is becoming an important cause of morbidity and mortality especially in developing countries with lower health status indices. Also, the high prevalence of multi-drug resistant strains of bacteria has elevated the threat of untreatable bacterial infections and adds urgency to the hunt for new healing strategies (Isaka et al, 2017). In addition to this problem, antibiotics are sometimes associated with adverse effects on the host, which include hypersensitivity, depletion of beneficial gut and mucosal microorganism, immune suppression and allergic reactions (Namita & Mukesh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The study was inspired by the widespread ethnomedicinal use of the plant N. macrophylla in the management of snakebite, microbial infections, pain, and anti-inflammatory diseases. Preliminary results provided promising results and validated the ethnomedicinal claims [25] . Inspired by these results, the ethylacetate soluble fraction of the methanol stem bark extract which appeared to be promising was subjected to chromatographic studies in order to isolate and evaluate bioactive compound(s) responsible for the observed antivenom, analgesic, antiinflammatory, and antimicrobial effects.…”
Section: Discussionmentioning
confidence: 56%
“…GC-MS analysis of the chloroform leaf extract of N. macrophylla revealed the presence of flavonoids, steroids, palmitoleic acid, tannins, glycosides, alpha and beta tacopherol [25]. Pharmacological actions of the stem bark of N. macrophylla has been confined to analgesic [23], antimicrobial [24] and antivenom [25] activities; Isaka et al [25] has reported the antimicrobial activity of the ethanol leaf extract of the plant; the extracts and fractions of N. macrophylla leaf exhibited remarkable antibacterial and antibiofilm activities against S. aureus and P. aeruginosa [26]. Antimicrobial activity of stigmasterol from the stem bark of the plant has also been reported [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nm seed cake contains tannins, flavonoids and alkaloids [17]. Carbohydrates, alkaloids, flavonoids, anthraquinones tannins, saponins, glycosides, steroids and triterpenes were reported to be present in the methanol stem bark extract of Nm [37].…”
Section: Flavonoidsmentioning
confidence: 99%
“…The methanol stem bark extract of Nm showed good antimicrobial effect against some clinical isolates including S. pyogenes, S. feacalis, B. subtilis, B. cereus, E. coli, P. fluorescence, C. albicans and C. krusei with MIC and MBC/MFC values ranging from 2.5 -5.0 mg/mL and 5 -20 mg/mL, respectively [37]. Moreover, stigmasterol from the stem bark of Nm exhibited a broad-spectrum antimicrobial activity against methicillin-resistant S. aureus (MRSA), vancomycin-resistant enterococci (VRE), S. aureus, S. faecalis, E. coli, S. typhimurium, P. fluorescens, K. pneumoniae, C. albicans and C. krusei with MIC and MBC/MFC values ranging from 6.25 -25 μg/mL and 12.5 -50 μg/mL, respectively [41].…”
Section: Biological and Pharmacological Properties Of Nmmentioning
confidence: 99%